2019
DOI: 10.3390/app9020304
|View full text |Cite
|
Sign up to set email alerts
|

PPG-Based Systolic Blood Pressure Estimation Method Using PLS and Level-Crossing Feature

Abstract: This paper proposes a cuff-less systolic blood pressure (SBP) estimation method using partial least-squares (PLS) regression. Level-crossing features (LCFs) were used in this method, which were extracted from the contour lines arbitrarily drawn on the second-derivative photoplethysmography waveform. Unlike conventional height ratio features (HRFs), which are extracted on the basis of the peaks in the waveform, LCFs can be reliably extracted even if there are missing peaks in the waveform. However, the features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In the study [27], the authors analyze PPG data that were obtained from the right forefinger of healthy people and propose a method for improving the accuracy of blood pressure measurement.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the study [27], the authors analyze PPG data that were obtained from the right forefinger of healthy people and propose a method for improving the accuracy of blood pressure measurement.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Feature extraction plays significant role in traditional ML, extracting valid and informative features that are most relevant to the prediction task is crucial for training an accurate prediction model. Therefore, features [22], [24], [27], [37], [55] were systematically extract from PPG and ECG signals.…”
Section: Feature Extractionmentioning
confidence: 99%
“…S et al [21] used Kmeans singular value decomposition (K-SVD) as an alternative method of feature extraction to learn the sparse representation of the signal from PPG and then use the learned sparse representation as features to train a prediction model. Fujita et al [22] extracted level-crossing features (LCFs) from the second derivative waveform of PPG, and then these LCFs were used to train a partial least-squares regression model. The results exhibited that this model is superior to multiple regression analysis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into arterial stiffness has reported on age, vasoactive drugs, diseases such as arteriosclerosis and diabetes, and changes in PPG waveforms [18]. Moreover, substantial research is being conducted on cuff-less blood pressure estimation using PPG waveform features [2], [19], [20]. To obtain detailed features from PPG waveforms, these research efforts used a dedicated sensor at a comparatively high sampling rate for PPG measurement.…”
Section: Introductionmentioning
confidence: 99%